The value of blood lactate and lactate clearance rate in evaluating the prognosis of athletes with heat illness of varying degrees after high-intensity exercise - Li Yu; Xuehui Dong; Huanhuan Li; Lili Mi (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Heat stroke, a severe heat illness with organ damage, is a major cause of cause irreparable organ damage and higher death rates among military persons and athletes. Objectives To study the changes in blood lactate (Lac) levels and lactate clearance rate (LCR) in athletes with heat illness of varying degrees after high-intensity exercise and to evaluate their prognostic value. Material and methods In present study, acute care unit admitted 36 heat sickness patients following high-intensity exercise from December 2019 to July 2024, with comprehensive medical records, for retrospective study. The study population consisted of two groups of high level athletes: the favourable Prognosis Group (< 7 days, 22 cases), comprising 21 males and 1 female with a mean age of 21.8 ± 2.7 years, and the bad Prognosis Group (≥ 7 days, 14cases), consisting of 14 males with a mean age of 22.6 ± 3.2 years. Lac levels were assessed at admission (0 h) and early in therapy (2 h, 6 h), and the LCR was computed. Lac and LCR values at each time point were compared between the two groups to see how they affected patient prognosis. Results After 2 and 6 h of therapy, lactate levels decreased significantly in the good prognosis group (1.2 ± 0.5 mmol/L at 2 h and 0.8 ± 0.3 mmol/L at 6 h), but remained elevated in the poor prognosis group (4.2 ± 1.2 mmol/L at 2 h and 3.5 ± 1.5 mmol/L at 6 h). Core body temperature normalized in both groups, but the good prognosis group showed a more rapid decline, with temperatures of 37.4 ± 0.6 °C at 2 h and 36.8 ± 0.4 °C at 6 h in the good prognosis group, and 38.8 ± 0.8 °C at 2 h and 38.2 ± 0.9 °C at 6 h in the poor prognosis group. Notably, a significant positive correlation existed between lactate levels and APACHE II scores at admission (P < 0.01). Furthermore, logistic regression analysis revealed that the 2-hour lactate clearance rate (LCR) (R2 = 0.83) was an independent predictor of outcomes. Conclusions The study suggests that athletes with elevated lactate levels after heat illness may be at higher risk of adverse outcomes. The 2-hour lactate clearance rate (LCR) appears to be a valuable prognostic indicator, with potential applications in evaluating the severity of heat illness and guiding treatment decisions. Furthermore, dynamic monitoring of lactate levels in conjunction with LCR may provide valuable insights into the clinical management and prognosis of athletes with heat-related illnesses.